2016
DOI: 10.12659/pjr.895827
|View full text |Cite
|
Sign up to set email alerts
|

Common and Uncommon Anatomical Variants of Intrahepatic Bile Ducts in Magnetic Resonance Cholangiopancreatography and its Clinical Implication

Abstract: SummaryBackgroundPreoperative knowledge of intrahepatic bile duct (IHD) anatomy is critical for planning liver resections, liver transplantations and complex biliary reconstructive surgery. The purpose of our study was to demonstrate the imaging features of various anatomical variants of IHD using magnetic resonance cholangio-pancreatography (MRCP) and their prevalence in our population.Material/MethodsThis observational clinical evaluation study included 224 patients who were referred for MRCP. MRCP was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 18 publications
4
35
3
1
Order By: Relevance
“…Among seven types of anatomic variants, type 3a with drainage of the RP duct into the LHD was the most common, followed by type 2 (trifurcation), which were present in 16.8% and 13.9% of PD patients, respectively. These rates for control group were 20.4% and 5.1%, respectively, and were compatible with those reported in previous studies (8,14,(20)(21)(22). The most common complications after hepatobiliary surgeries are related to the iatrogenic injuries of bile ducts.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among seven types of anatomic variants, type 3a with drainage of the RP duct into the LHD was the most common, followed by type 2 (trifurcation), which were present in 16.8% and 13.9% of PD patients, respectively. These rates for control group were 20.4% and 5.1%, respectively, and were compatible with those reported in previous studies (8,14,(20)(21)(22). The most common complications after hepatobiliary surgeries are related to the iatrogenic injuries of bile ducts.…”
Section: Discussionsupporting
confidence: 91%
“…Sarawagi et al (8) reported similar findings in their study. Since ligation or resection of the aberrant duct may lead to complications such as bile leakage, biliary bilioma, and bile peritonitis, knowledge of variations of the right hepatic duct draining into the cystic duct (type 4) is critical.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Due to the labyrinth-like anatomy of the biliary system and frequent anatomical variants [5], the inexperienced operator may be easily confused while performing choledochoscopic examinations. Thus, trainees usually require longer training periods to achieve familiarity with these techniques and to become comfortable with the complex anatomy of the biliary system.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this case, the segment II bile duct was conveying right lobe posterior segment bile duct instead of being a single duct. The prevalence of type 3A variation of the right biliary duct according to the classification of Huang et al was reported as 14.5%-27.6% (3,4). In the meanwhile, the prevalence of the type 2 variation of the left biliary duct according to the classification of Cho et al (2) was 23.2%-30%.…”
Section: Images Of the Issuementioning
confidence: 97%